Efficacy of nano-silicon in the control of chocolate spot disease of Vicia faba L. caused by Botrytis fabae. Issue 1 (1st January 2020) - Hasan, Khadiga A.; Soliman, Hoda; Baka, Zakaria; Shabana, Yasser M.
ABSTRACT: The effect of nano-silicon (NSi) at concentrations of 1.5 and 3mM in controlling the chocolate spot disease of Vicia faba L. was investigated. Botrytis fabae the causal of chocolate spot disease was isolated from infested leaves of faba bean collected from different fields of Dakahlia governorate in the winter of 2016. B. fabae isolated from Elsinbilawin (isolate B1) showed the maximum rates of disease severity (DS) and disease incidence (DI). The application of NSi caused a significant reduction in DS and DI of faba bean chocolate spot. Infection with B. fabae caused a great loss in chloroplasts number per mesophyll cell and changed the ultrastructure of chloroplasts. However, NSi-treated plants showed a significant increase in chloroplast, cell wall thickness, while the other cell organelles were kept in a good shape. In addition, NSi treatment enhanced the accumulation of proline and increased the total phenols. It also improved the activities of protective enzymes, peroxidase (POD) and polyphenol oxidase (PPO) comparing with the untreated control. Besides, it enhanced the accumulation of protein in infected plants in comparison with the pathogen-alone treatment. Under energy dispersive X-ray analysis (EDX), the NSi-treated plants showed a significant increase in silicon concentration that protects the plant from external damaging factors.